A high-toughness optical transparent adhesive for folding screens and its preparation method and application
The bonus reactions of the alcohol compound and the end hydroxide polytthne and the free radical polymerization of polyacrylate are prepared to prepare high tough optical transparent glue to solve the difficulty of high toughness and resistance in the application of the existing optical transparent glue in the application of folding screen applications. The requirements of bending, creep resistance and low temperature resistance have achieved excellent performance.
Patent Information
- Application Number
- CN202211740151.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-31
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2042-12-31
AI Technical Summary
When used in folding screens, existing optical transparent gels are difficult to meet the requirements of high toughness, bending resistance, creep resistance and low temperature resistance.
The isocyanate-terminated polybutadiene is generated through the addition reaction of isocyanate compounds and hydroxyl-terminated polybutadiene as a macromolecular cross-linking agent, and is mixed with the polyacrylate containing side hydroxyl groups prepared by free radical polymerization to prepare High toughness optically clear glue.
The optical transparency of the income has excellent performance such as high toughness, creep resistance, bending resistance, and low temperature resistance. It can maintain good adhesion performance without multiple dynamic bending and high -intensity repeated folding.
Smart Images

Figure BDA0004033051280000021 
Figure BDA0004033051280000051 
Figure BDA0004033051280000151
Abstract
Description
Technical Field
[0001] The present invention provides a high-toughness optically transparent adhesive for a folding screen and a preparation method and application thereof, belonging to the technical field of optical display materials. Background Art
[0002] Optical Clear Adhesive (OCA), also known as optical clear adhesive, is an adhesive that can improve the color contrast of the screen and thus improve the image display quality. As one of the important components of today's touch screen mobile phones, it has the advantages of high bonding strength, good optical performance, and good durability. It has been widely used in high-tech electronic industries such as televisions, mobile phones, and tablet computers. Optical clear adhesive can be divided into polyacrylate OCA, polyurethane OCA, silicone OCA, etc. according to its main chain structure. Among them, polyacrylate OCA is the most widely used because it can use a variety of monomers as raw materials and is easy to copolymerize and control.
[0003] With the development of modern science and technology, mobile phone displays have evolved from flat screens to foldable screens, which has led to new technical requirements for optically transparent adhesives. OCA used in foldable screens is usually required to have better toughness, avoid wrinkles and creep as much as possible during the folding process, and have good adhesion under various conditions to meet the needs of foldable screens to resist bending; OCA is also required to have a lower glass transition temperature to increase cold resistance. Therefore, the synthesis of optically transparent adhesives that are resistant to bending, creep, low temperature, and excellent in adhesion has become a technical problem that needs to be overcome urgently.
[0004] HTPB, also known as hydroxy-terminated polybutadiene (HTPB for short), is a polymer with a non-polar polybutadiene carbon chain as the main chain and hydroxyl groups at the chain end. Due to its good toughness, low temperature resistance and low viscosity, it is often used as an adhesive for solid propellants in rockets and missiles.
[0005] There are reports in the prior art that end-hydroxyl polybutadiene is used to prepare optically transparent adhesives. For example, Chinese patent document CN104231996A discloses a liquid optically transparent adhesive for a fully laminated module and a preparation method thereof. The transparent adhesive is composed of the following substances in parts by weight: 0 to 40 parts of polybutadiene-polyether block acrylic resin or polybutadiene-polyether block methacrylic resin, 0 to 30 parts of acrylic resin or methacrylic resin, 0 to 25 parts of acrylic acid active diluent or methacrylic acid active diluent, 0 to 30 parts of inert plasticizer, 0 to 10 parts of photoinitiator, and 0 to 2 parts of antioxidant. The liquid optically transparent adhesive of the invention has low curing shrinkage, low thermal stress, low modulus of the cured product, good flexibility, and high adhesion. When laminating ultra-thin screens or large-size screens, it is easier to avoid deformation of the screen due to stress. However, the invention mainly focuses on the research of optical properties, and does not disclose the relevant effect data such as toughness, creep resistance, bending resistance, and low temperature resistance of the obtained optically transparent adhesive.
[0006] Therefore, there is an urgent need to develop an optically transparent adhesive with high toughness, bending resistance, creep resistance, and low temperature resistance to meet the requirements of folding screens. Summary of the invention
[0007] In view of the deficiencies in the prior art, the present invention provides a high-toughness optically transparent adhesive for folding screens, and a preparation method and application thereof. The present invention adopts an isocyanate compound and a polybutadiene containing terminal hydroxyl groups to carry out an addition reaction to generate a polybutadiene containing terminal isocyanate groups as a macromolecular crosslinking agent, and then mixes it with a polyacrylate containing side hydroxyl groups prepared by free radical polymerization to obtain an optically transparent adhesive. The obtained optically transparent adhesive is applied to folding screens, and after curing, a transparent cross-linked polymer is obtained, which has excellent properties such as high toughness, creep resistance, bending resistance, and low temperature resistance.
[0008] To achieve the above objectives, the technical solutions of the present invention are as follows:
[0009] A high-toughness optically transparent adhesive for a folding screen, comprising the following components: isocyanate-terminated polybutadiene, polyacrylate, and an organic diluent;
[0010] The isocyanate-terminated polybutadiene is prepared from the following raw materials in parts by weight: 5-50 parts of hydroxyl-terminated polybutadiene, 10-100 parts of isocyanate compounds, and 50-200 parts of solvent A;
[0011] The polyacrylate is prepared from the following raw materials in parts by weight: 30-90 parts of a first acrylic acid ester monomer, 0.1-15 parts of a second acrylic acid ester monomer containing active hydrogen, 0.02-4 parts of an initiator, and 20-260 parts of a solvent B.
[0012] Preferably, according to the present invention, the isocyanate-terminated polybutadiene is prepared from the following raw materials in parts by weight: 5-15 parts of hydroxyl-terminated polybutadiene, 10-30 parts of isocyanate compounds, and 50-70 parts of solvent A;
[0013] The polyacrylate is prepared from the following raw materials in parts by weight: 40-80 parts of a first acrylic acid ester monomer, 0.15-10 parts of a second acrylic acid ester monomer containing active hydrogen, 0.025-3.725 parts of an initiator, and 40-60 parts of a solvent B.
[0014] According to the preferred embodiment of the present invention, the organic diluent is one or a combination of two or more of toluene, tetrahydrofuran, 1,4-dioxane, dichloromethane, chloroform or anhydrous ether.
[0015] Preferably, according to the present invention, the mass ratio of the isocyanate-terminated polybutadiene to the polyacrylate is 1-4.5:1; the ratio of the mass of the organic diluent to the total mass of the isocyanate-terminated polybutadiene and the polyacrylate is 1:1-3.
[0016] According to the preferred embodiment of the present invention, the hydroxy-terminated polybutadiene has the following structure:
[0017]
[0018] Wherein, x = 1-1000, y = 1-200, z = 1-100. The hydroxy-terminated polybutadiene is commercially available.
[0019] Preferably according to the present invention, the isocyanate compound is one or a combination of two or more of diphenylmethane diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate or toluene diisocyanate.
[0020] Preferably according to the present invention, solvent A is one or a combination of two or more of toluene, acetone, methanol, ethanol, tetrahydrofuran, cyclohexane, ethyl acetate, isopropanol, dichloromethane or chloroform.
[0021] According to the present invention, the first acrylic acid ester monomer is preferably one or a combination of two or more of methyl acrylate, ethyl acrylate, n-butyl methacrylate, isobutyl methacrylate, n-octyl acrylate, methyl methacrylate, ethyl methacrylate, isopropyl methacrylate, hexyl methacrylate, isooctyl acrylate or glycidyl methacrylate.
[0022] According to the present invention, the active hydrogen-containing acrylic acid ester second monomer is one or a combination of two or more of acrylamide, acrylic acid, hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxybutyl acrylate, 2-hydroxybutyl acrylate, hydroxypropyl methacrylate, hydroxyhexyl acrylate or hydroxyethyl methacrylate.
[0023] According to the present invention, the initiator is preferably one or a combination of two or more of azobisisobutyronitrile, azobisisovaleronitrile, azobisisoheptanenitrile, cyclohexanone peroxide, dibenzoyl peroxide or tert-butyl hydroperoxide.
[0024] According to the preferred embodiment of the present invention, solvent B is one or a combination of two or more of ethyl acetate, petroleum ether, methanol, ethanol, dichloromethane, toluene, anhydrous ether or tetrahydrofuran.
[0025] The method for preparing the above-mentioned high-toughness optically transparent adhesive for folding screens comprises the steps of:
[0026] (1) In solvent A, terminal hydroxyl polybutadiene and isocyanate compound are subjected to addition reaction to prepare terminal isocyanate polybutadiene;
[0027] (2) In solvent B, under the action of an initiator, a first acrylate monomer and a second acrylate monomer containing active hydrogen undergo a free radical polymerization reaction to prepare a polyacrylate;
[0028] (3) Evenly mix the isocyanate-terminated polybutadiene, polyacrylate and organic diluent, and remove bubbles to obtain an optically transparent adhesive.
[0029] Preferably according to the present invention, in step (1), the addition reaction temperature is 60-150° C., and the addition reaction time is 5-12 h.
[0030] Preferably, in step (1), the post-treatment method of the reaction solution obtained by the addition reaction is as follows: the reaction solution is concentrated to half of the original volume by rotary evaporation, and petroleum ether is added to precipitate a solid product; the solid product is taken and dissolved by adding chloroform; and then all solvents are removed by rotary evaporation to obtain the isocyanate-terminated polybutadiene.
[0031] Preferably according to the present invention, in step (2), the free radical polymerization reaction temperature is 20-90° C., and the reaction time is 5-12 h.
[0032] Preferably, in step (2), the post-treatment method of the reaction solution obtained by the free radical polymerization reaction is as follows: the reaction solution is concentrated by rotary evaporation to half of the original volume, methanol is added to precipitate a solid product; the solid product is taken and dissolved by adding chloroform; and then all the solvent is removed by rotary evaporation to obtain polyacrylate.
[0033] Preferably, in step (3) of the present invention, the preparation of the optically transparent adhesive comprises the steps of: mixing the isocyanate-terminated polybutadiene, polyacrylate and an organic diluent, stirring at room temperature for 0.5-2 hours, and then degassing by vacuum to obtain the optically transparent adhesive.
[0034] The above-mentioned high-toughness optically transparent adhesive for folding screens is used in folding screens.
[0035] According to a preferred embodiment of the present invention, the optically transparent adhesive is cured as follows: curing at room temperature for 10-15 hours, and then curing at 100-120° C. for 1-8 hours.
[0036] The curing route of the optically transparent adhesive of the present invention is schematically shown as follows:
[0037]
[0038] in,
[0039] x=1-1000, y=1-200, z=1-100, m=1-100, n=1-100.
[0040] R1=-(CH2)6-,
[0041] R2=-OCH3,-OCH2CH3,-OCH2CH2CH2CH3,-OCH2CH(CH3)CH3,-OCH2CH(CH2CH3)CH2CH2CH2CH3,-OCH2CH2CH2CH2CH2CH2CH2CH3,-OCH(CH3)CH3,-OCH2CH2CH2CH2CH2CH3,
[0042] R3=-H, -CH3.
[0043] R4=-NH2, -OH, -O(CH2)2OH, -OCH(CH3)CH2OH, -O(CH2)4OH, -OCH2CH(OH)CH2CH3, -O(CH2)6OH.
[0044] R5=-H, -CH3.
[0045] R6=-NH-, -O-, -O(CH2)2O-, -OCH(CH3)CH2O-, -O(CH2)4O-, -OCH2CH(CH2CH3)O-, -O(CH2)6O-.
[0046] The technical features and beneficial effects of the present invention are as follows:
[0047] 1. The present invention reacts the hydroxyl group of HTPB with an isocyanate compound to generate an urethane group to obtain an end-functionalized polybutadiene liquid rubber oligomer, which is used as a macromolecular crosslinking agent to form an optically transparent adhesive with polyacrylate; the optically transparent adhesive is cured to obtain a polyacrylate crosslinked with a polybutadiene molecular chain. The present invention introduces a polybutadiene molecular chain segment at the molecular level to improve the toughness, low temperature resistance, bending resistance, creep resistance and other properties of the polyacrylate. At the same time, the urethane chain segment is easy to form an intermolecular hydrogen bond, which increases the crosslinking density of the material and further improves the toughness, creep resistance, bending resistance and other properties of the material. The polyacrylate of the present invention is prepared by free radical polymerization using two types of acrylate monomers; compared with one type of synthesized polyacrylate, the polyacrylate of the present invention can effectively adjust the crosslinking density of the material as well as the low temperature resistance, mechanical properties and other properties of the material; at the same time, another type of acrylate monomer containing active hydrogen can provide a crosslinking point for the macromolecular crosslinking agent, introduce a rubber component, and improve the mechanical properties of the material such as flexibility.
[0048] 2. The raw material components of the optical transparent adhesive of the present invention act together as a whole, combined with a specific preparation method, to prepare the optical transparent adhesive of the present invention; after the optical transparent adhesive is cured, the various groups in the polymer material act together to achieve the excellent effects of the present invention, that is, high toughness, bending resistance, creep resistance, low temperature resistance, and excellent bonding performance. The types and proportions of the first acrylate monomer and the second acrylate monomer containing active hydrogen, the proportion of terminal isocyanate polybutadiene and polyacrylate, the proportion of terminal hydroxyl polybutadiene and isocyanate compounds, and the types of isocyanate compounds of the present invention will have a certain impact on the performance of the obtained optical transparent adhesive. If the above conditions are not suitable, the excellent effects of the present invention cannot be achieved.
[0049] 3. The optically transparent adhesive of the present invention has excellent bending resistance after curing. The dynamic bending of the folding screen mobile phones OPPO Find X and Samsung's Galaxy Z Fold 3 on the market is only 200,000 times. The optically transparent adhesive of the present invention can withstand more than 300,000 dynamic bendings after curing, and has excellent bending resistance.
[0050] 4. The shear creep of the optically transparent adhesive after curing is as low as 5.3%, which enables it to be applied to folding screens. The folding screens will not separate from the bonded components due to stress concentration during the folding process, and can withstand repeated folding times with high intensity. Due to the increase in cross-linking density, deformation is not easy to occur, and the creep amount is reduced, meeting the creep resistance requirements of folding screens.
[0051] 5. The lowest glass transition temperature of the material obtained after curing the optically transparent adhesive of the present invention is -50°C. 3M OCA is the most commonly used in the market, and the commonly used model is 8146-2, and its lowest glass transition temperature is -40°C. Therefore, the cold resistance of the material obtained after curing the optically transparent adhesive of the present invention is better than that of the OCA on the market. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 is the H NMR spectrum of isocyanate-terminated polybutadiene (ITPB) in Example 1; the abscissa is the chemical shift;
[0053] Figure 2 It is the infrared spectrum of the isocyanate-terminated polybutadiene (ITPB) and the hydroxyl-terminated polybutadiene (HTPB) in Example 1; the abscissa is the wavelength and the ordinate is the transmittance;
[0054] Figure 3 It is the GPC spectrum of the isocyanate-terminated polybutadiene (ITPB) and the hydroxyl-terminated polybutadiene (HTPB) in Example 1; the abscissa is the retention time;
[0055] Figure 4 is the H NMR spectrum of polyacrylate (PA) in Example 1; the abscissa is the chemical shift;
[0056] Figure 5 is the infrared spectrum of polyacrylate (PA) in Example 1; the abscissa is the wavelength, and the ordinate is the transmittance;
[0057] Figure 6 It is a comparison chart of creep properties of polyacrylate cured products prepared in Examples 1-4 and Comparative Example 1; the abscissa is time and the ordinate is strain rate;
[0058] Figure 7 It is a dynamic thermomechanical analysis comparison diagram of the polybutadiene cross-linked acrylate cured product (ITPB-PA-1) in Example 1; the abscissa is temperature. DETAILED DESCRIPTION
[0059] The present invention will be further described below with reference to specific embodiments, but is not limited thereto.
[0060] Meanwhile, the experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0061] The molecular weight Mn of the hydroxy-terminated polybutadiene used in the examples is 3000-3600 and is available from Tianyuan Junrong Chemical Research Institute New Materials Incubator Co., Ltd.
[0062] Example 1
[0063] A high-toughness optical transparent adhesive for folding screens, comprising the following components: 1g of isocyanate-terminated polybutadiene, 1g of polyacrylate, and 2g of organic diluent toluene;
[0064] The isocyanate-terminated polybutadiene is prepared from the following raw materials in parts by weight: 10 g of hydroxyl-terminated polybutadiene, 20 g of isophorone diisocyanate, and 60 g of solvent A, toluene;
[0065] The polyacrylate is prepared from the following raw materials in parts by weight: 40 g of isooctyl acrylate, a first monomer of acrylate, 10 g of hydroxybutyl acrylate, a second monomer of acrylate containing active hydrogen, 0.025 g of azobisisobutyronitrile, an initiator, and 50 g of ethyl acetate, a solvent B.
[0066] The method for preparing the above-mentioned high-toughness optically transparent adhesive for folding screens comprises the steps of:
[0067] (1) Dissolve 40 g of isooctyl acrylate, 10 g of hydroxybutyl acrylate, and 0.025 g of azobisisobutyronitrile in 50 g of ethyl acetate, place in a three-necked flask equipped with a spherical condenser, heat under reflux at 65°C for 5 h, concentrate by rotary evaporation to half of the initial volume, and then precipitate the product with methanol. After standing, pour out the supernatant, and then add 10 ml of chloroform to dissolve it. Remove all solvents by rotary evaporation to obtain polyacrylate. The yield is 85%.
[0068] (2) 10 g of hydroxy-terminated polybutadiene was placed in a 100 ml three-necked flask, 30 g of toluene was added thereto, and after stirring at room temperature for half an hour, 20 g of isophorone diisocyanate was added and dissolved in 30 g of toluene, and the mixture was fully mixed, refluxed at 80° C. for 5 h, and concentrated by rotary evaporation to half of the original volume, 100 ml of petroleum ether was added thereto to precipitate the product, and after standing, the supernatant was poured out, and 20 ml of chloroform was added thereto to dissolve. All solvents were removed by rotary evaporation to obtain isocyanate-terminated polybutadiene.
[0069] (3) Mix 1 g of the above polyacrylate with 1 g of isocyanate-terminated polybutadiene, add 2 g of anhydrous toluene to adjust the viscosity to a suitable value for scraper coating, stir at room temperature for 30 min, and remove bubbles in vacuum to obtain an optically transparent adhesive.
[0070] The preparation method of polyacrylate cured product (ITPB-PA-1) based on isophorone diisocyanate polybutadiene cross-linking comprises the following steps:
[0071] The optically transparent adhesive was coated on a 40 μm thick release film, and the coated sample was placed in a fume hood overnight (i.e., at room temperature for 12 h), and then cured at 100°C for 2 h to obtain an isophorone diisocyanate-polybutadiene cross-linked polyacrylate cured product (ITPB-PA-1) with a thickness of 200 μm.
[0072] Figure 1 This is the H NMR spectrum of the isocyanate-terminated polybutadiene (ITPB) in this example. As can be seen from the figure, hydrogen 4 (-NH-CH2-) and hydrogen 6 (-CH2-O-) connected to carbamate appeared at δ = 3.24ppm and δ = 4.09ppm, and the integral of the two is 1:0.85, which is consistent with the theoretical value of 1:1, indicating that the isocyanate-terminated polybutadiene was successfully synthesized. The NMR data are as follows:
[0073] 1 H NMR (400MHz, CDCl3, ppm): 0.94ppm (3H, s, -CH3), 3.36ppm (1H, s, -CH-NCO), 1.43ppm (2H , m, -CH2-), 3.23ppm (2H,s, -NH-CH2-), 5.56ppm (1H,s, -NH-), 4.09ppm (2H,s, -CH2-O-).
[0074] Figure 2 The infrared spectra of the isocyanate-terminated polybutadiene (ITPB) and the hydroxyl-terminated polybutadiene (HTPB) in this embodiment are shown in the figure. -1 The characteristic peaks corresponding to hydroxyl groups disappeared completely, and the peaks at 2250 cm -1 and 1725cm -1 The characteristic peaks of isocyanate and carbonyl groups appeared, indicating that all hydroxyl groups had reacted and isocyanate-terminated polybutadiene was successfully synthesized.
[0075] Figure 3 It is the GPC spectrum of the terminal isocyanate polybutadiene (ITPB) and the terminal hydroxyl polybutadiene (HTPB) in this embodiment. The retention time of the terminal hydroxyl polybutadiene is 16min. Since the molecular weight of the terminal isocyanate polybutadiene generated by the reaction increases, the retention time is shortened to 14.7min. The Mn and PDI of the terminal hydroxyl polybutadiene and the terminal isocyanate polybutadiene are 3520, 1.92 and 4200, 2, respectively. It can be seen from the figure that the terminal isocyanate polybutadiene is successfully synthesized.
[0076] Figure 4 This is the nuclear magnetic hydrogen spectrum of the polyacrylate (PA) in this example. It can be seen from the figure that two characteristic peaks of hydrogen on the carbon-carbon single bond appear at δ = 4.99ppm and δ = 5.42ppm, respectively, hydrogen No. 2 (-CH-) and hydrogen No. 1 (-CH-), and the integral is 9:1.05, which is consistent with the theoretical value of 9:1, indicating that the polyacrylate was successfully synthesized;
[0077] The NMR data are as follows:
[0078] 1 H NMR (400MHz, CDCl3, ppm): 5.42ppm (1H,s,-CH-), 4.99ppm (1H,s,-CH-), 2.08ppm (1H,s,O-CH2-).
[0079] Figure 5 This is the infrared spectrum of polyacrylate (PA) in this example. As can be seen from the figure, at 1638cm -1 The characteristic peak corresponding to the carbon-carbon double bond completely disappeared, and the peak at 3546 cm -1 The characteristic peak of hydroxyl group appeared, indicating that all carbon-carbon double bonds had reacted, indicating that polyacrylate was successfully synthesized.
[0080] Example 2
[0081] A high-toughness optical transparent adhesive for folding screens, comprising the following components: 1g of isocyanate-terminated polybutadiene, 1g of polyacrylate, and 2g of organic diluent toluene;
[0082] The isocyanate-terminated polybutadiene is prepared from the following raw materials in parts by weight: 10 g of hydroxyl-terminated polybutadiene, 20 g of isophorone diisocyanate, and 60 g of solvent A, toluene;
[0083] The polyacrylate is prepared from the following raw materials in parts by weight: 40 g of methyl acrylate, a first monomer of acrylic esters, 10 g of hydroxybutyl acrylate, a second monomer of acrylic esters containing active hydrogen, 0.025 g of azobisisobutyronitrile, an initiator, and 50 g of ethyl acetate, a solvent B.
[0084] The method for preparing the above-mentioned high-toughness optically transparent adhesive for folding screens comprises the steps of:
[0085] (1) 40 g of methyl acrylate, 10 g of hydroxybutyl acrylate, and 0.025 g of azobisisobutyronitrile were dissolved in 50 g of ethyl acetate, placed in a three-necked flask equipped with a spherical condenser, heated under reflux at 20°C for 5 h, concentrated by rotary evaporation to half of the initial volume, and then precipitated with methanol to precipitate the product. After standing, the supernatant was poured out, and 10 g of chloroform was added to dissolve it. All solvents were removed by rotary evaporation to obtain polyacrylate. The yield was 83.5%.
[0086] (2) 10 g of hydroxy-terminated polybutadiene was placed in a 100 ml three-necked flask, 30 g of toluene was added thereto, and after stirring at room temperature for half an hour, 20 g of isophorone diisocyanate was added and dissolved in 30 g of toluene, and the mixture was fully mixed, refluxed at 80° C. for 5 h, and concentrated to half of the original volume by vacuum distillation, 100 ml of petroleum ether was added thereto to precipitate the product, and after standing, the supernatant was poured out, and 20 ml of chloroform was added thereto to dissolve. All solvents were removed by rotary evaporation to obtain isocyanate-terminated polybutadiene.
[0087] (3) Mix 1 g of the above polyacrylate with 1 g of isocyanate-terminated polybutadiene, add 2 g of anhydrous toluene to adjust the viscosity to a suitable value for scraper coating, stir at room temperature for 30 min, and remove bubbles in vacuum to obtain an optically transparent adhesive.
[0088] The preparation method of polyacrylate cured product (ITPB-PA-2) based on isophorone diisocyanate polybutadiene cross-linking comprises the following steps:
[0089] The optically transparent adhesive was coated on a 40 μm thick release film, and the coated sample was placed in a fume hood overnight (i.e., at room temperature for 12 h), and then cured at 100° C. for 2 h to obtain an isophorone diisocyanate-polybutadiene cross-linked polyacrylate cured product (ITPB-PA-2) with a thickness of 200 μm.
[0090] Example 3
[0091] A high-toughness optical transparent adhesive for folding screens, comprising the following components: 1g of isocyanate-terminated polybutadiene, 1g of polyacrylate, and 2g of organic diluent toluene;
[0092] The isocyanate-terminated polybutadiene is prepared from the following raw materials in parts by weight: 10 g of hydroxyl-terminated polybutadiene, 20 g of hexamethylene diisocyanate, and 60 g of solvent A, toluene;
[0093] The polyacrylate is prepared from the following raw materials in parts by weight: 60 g of ethyl acrylate, a first monomer of acrylate, 10 g of hydroxyethyl acrylate, a second monomer of acrylate containing active hydrogen, 0.025 g of azobisisovaleronitrile as an initiator, and 50 g of ethyl acetate as a solvent B.
[0094] The method for preparing the above-mentioned high-toughness optically transparent adhesive for folding screens comprises the steps of:
[0095] (1) 60 g of ethyl acrylate, 10 g of hydroxyethyl acrylate, and 0.025 g of azobisisovaleronitrile were dissolved in 50 g of ethyl acetate, placed in a three-necked flask equipped with a spherical condenser, heated under reflux at 60°C for 5 h, concentrated by rotary evaporation to half of the initial volume, and then precipitated with methanol to precipitate the product. After standing, the supernatant was poured out, and 10 ml of chloroform was added to dissolve it. All solvents were removed by rotary evaporation to obtain polyacrylate. The yield was 86%.
[0096] (2) 10 g of hydroxyl-terminated polybutadiene was placed in a 100 ml three-necked flask, 30 g of toluene was added thereto, and after stirring at room temperature for half an hour, 20 g of hexamethylene diisocyanate was added and dissolved in 30 g of toluene, and the mixture was fully mixed, refluxed at 80° C. for 5 h, and concentrated to half of the original volume by vacuum distillation, 100 ml of petroleum ether was added thereto to precipitate the product, and after standing, the supernatant was poured out, and 20 ml of chloroform was added thereto to dissolve. All solvents were removed by rotary evaporation to obtain isocyanate-terminated polybutadiene.
[0097] (3) Mix 1 g of the above polyacrylate with 1 g of isocyanate-terminated polybutadiene, add 2 g of anhydrous toluene to adjust the viscosity to a suitable value for scraper coating, stir at room temperature for 30 min, and remove bubbles in vacuum to obtain an optically transparent adhesive.
[0098] The preparation method of polyacrylate cured product (ITPB-PA-3) based on hexamethylene diisocyanate polybutadiene crosslinking comprises the following steps:
[0099] The optically transparent adhesive was coated on a 40 μm thick release film, and the coated sample was placed in a fume hood overnight (i.e., at room temperature for 12 h), and then cured at 100° C. for 2 h to obtain a 200 μm thick hexamethylene diisocyanate-polybutadiene cross-linked polyacrylate cured product (ITPB-PA-3).
[0100] Example 4
[0101] A high-toughness optical transparent adhesive for folding screens, comprising the following components: 1g of isocyanate-terminated polybutadiene, 1g of polyacrylate, and 2g of organic diluent toluene;
[0102] The isocyanate-terminated polybutadiene is prepared from the following raw materials in parts by weight: 10 g of hydroxyl-terminated polybutadiene, 20 g of hexamethylene diisocyanate, and 60 g of solvent A, toluene;
[0103] The polyacrylate is prepared from the following raw materials in parts by weight: 40 g of ethyl acrylate, a first monomer of acrylate, 10 g of hydroxyethyl acrylate, a second monomer of acrylate containing active hydrogen, 3.725 g of azobisisovaleronitrile as an initiator, and 50 g of ethyl acetate as a solvent B.
[0104] The method for preparing the above-mentioned high-toughness optically transparent adhesive for folding screens comprises the steps of:
[0105] (1) Dissolve 40 g of ethyl acrylate, 10 g of hydroxyethyl acrylate, and 3.725 g of azobisisovaleronitrile in 50 g of ethyl acetate, place in a three-necked flask equipped with a spherical condenser, heat under reflux at 80°C for 12 h, concentrate by rotary evaporation to half of the initial volume, and then precipitate the product with methanol. After standing, pour out the supernatant, and then add 10 ml of chloroform to dissolve it. Remove all solvents by rotary evaporation to obtain polyacrylate. The yield is 82.5%.
[0106] (2) 10 g of hydroxyl-terminated polybutadiene was placed in a 100 ml three-necked flask, 30 g of toluene was added thereto, and after stirring at room temperature for half an hour, 20 g of hexamethylene diisocyanate was added and dissolved in 30 g of toluene, and the mixture was fully mixed, refluxed at 80° C. for 5 h, and concentrated to half of the original volume by vacuum distillation, 100 ml of petroleum ether was added thereto to precipitate the product, and after standing, the supernatant was poured out, and 20 ml of chloroform was added thereto to dissolve. All solvents were removed by rotary evaporation to obtain isocyanate-terminated polybutadiene.
[0107] (3) Mix 1 g of the above polyacrylate with 1 g of isocyanate-terminated polybutadiene, add 2 g of anhydrous toluene to adjust the viscosity to a suitable value for scraper coating, stir at room temperature for 30 min, and remove bubbles in vacuum to obtain an optically transparent adhesive.
[0108] The preparation method of polyacrylate cured product (ITPB-PA-4) based on hexamethylene diisocyanate polybutadiene crosslinking comprises the following steps:
[0109] The optically transparent adhesive was coated on a 40 μm thick release film, and the coated sample was placed in a fume hood overnight (i.e., at room temperature for 12 hours), and then cured at 100° C. for 2 hours to obtain a 200 μm thick hexamethylene diisocyanate-polybutadiene cross-linked polyacrylate cured product (ITPB-PA-4).
[0110] Example 5
[0111] A high-toughness optical transparent adhesive for folding screens, comprising the following components: 1.5 g of isocyanate-terminated polybutadiene, 1 g of polyacrylate, and 2 g of organic diluent toluene;
[0112] The isocyanate-terminated polybutadiene is prepared from the following raw materials in parts by weight: 10 g of hydroxyl-terminated polybutadiene, 20 g of diphenylmethane diisocyanate, and 60 g of solvent A, toluene;
[0113] The polyacrylate is prepared from the following raw materials in parts by weight: 80 g of ethyl acrylate, a first monomer of acrylic esters, 0.15 g of acrylamide, a second monomer of acrylic esters containing active hydrogen, 2.5 g of azobisisovaleronitrile, an initiator, and 50 g of ethyl acetate, a solvent B.
[0114] The method for preparing the above-mentioned high-toughness optically transparent adhesive for folding screens comprises the steps of:
[0115] (1) Dissolve 80 g of ethyl acrylate, 0.15 g of acrylamide, and 2.5 g of azobisisovaleronitrile in 50 g of ethyl acetate, place in a three-necked flask equipped with a spherical condenser, heat under reflux at 80°C for 12 h, concentrate by rotary evaporation to half of the initial volume, and then precipitate the product with methanol. After standing, pour out the supernatant, and then add 10 ml of chloroform to dissolve it. Remove all solvents by rotary evaporation to obtain polyacrylate. Yield: 81%
[0116] (2) 10 g of hydroxy-terminated polybutadiene was placed in a 100 ml three-necked flask, 30 g of toluene was added thereto, and after stirring at room temperature for half an hour, 20 g of diphenylmethane diisocyanate was added and dissolved in 30 g of toluene, and the mixture was fully mixed, refluxed at 80° C. for 5 h, and concentrated to half of the original volume by vacuum distillation, 100 ml of petroleum ether was added thereto to precipitate the product, and after standing, the supernatant was poured out, and 50 ml of chloroform was added thereto to dissolve. All solvents were removed by rotary evaporation to obtain isocyanate-terminated polybutadiene.
[0117] (3) Mix 1 g of the above polyacrylate with 1.5 g of isocyanate-terminated polybutadiene, add 2 g of anhydrous toluene to adjust the viscosity to a suitable value for scraper coating, stir at room temperature for 30 min, and remove bubbles in vacuum to obtain an optically transparent adhesive.
[0118] The preparation method of polyacrylate cured product (ITPB-PA-5) based on diphenylmethane diisocyanate polybutadiene crosslinking comprises the following steps:
[0119] The optically transparent adhesive was coated on a 40 μm thick release film, and the coated sample was placed in a fume hood overnight (i.e., at room temperature for 12 hours), and then cured at 100° C. for 2 hours to obtain a 200 μm thick polyacrylate cured product (ITPB-PA-5) based on diphenylmethane diisocyanate polybutadiene cross-linking.
[0120] Example 6
[0121] A high-toughness optical transparent adhesive for folding screens, comprising the following components: 2.5 g of isocyanate-terminated polybutadiene, 1 g of polyacrylate, and 2 g of organic diluent toluene;
[0122] The isocyanate-terminated polybutadiene is prepared from the following raw materials in parts by weight: 10 g of hydroxyl-terminated polybutadiene, 20 g of diphenylmethane diisocyanate, and 60 g of solvent A, toluene;
[0123] The polyacrylate is prepared from the following raw materials in parts by weight: 80 g of ethyl acrylate, a first monomer of acrylic esters, 0.15 g of acrylamide, a second monomer of acrylic esters containing active hydrogen, 2.5 g of azobisisovaleronitrile, an initiator, and 50 g of ethyl acetate, a solvent B.
[0124] The method for preparing the above-mentioned high-toughness optically transparent adhesive for folding screens comprises the steps of:
[0125] (1) 80 g of ethyl acrylate, 0.15 g of acrylamide, and 2.5 g of azobisisovaleronitrile were dissolved in 50 g of ethyl acetate, placed in a three-necked flask equipped with a spherical condenser, heated to 80°C for 12 h under reflux, concentrated by rotary evaporation to half of the initial volume, and then precipitated with methanol to precipitate the product. After standing, the supernatant was poured out, and 10 ml of chloroform was added to dissolve it. All solvents were removed by rotary evaporation to obtain polyacrylate. The yield was 81%.
[0126] (2) 10 g of hydroxy-terminated polybutadiene was placed in a 100 ml three-necked flask, 30 g of toluene was added thereto, and after stirring at room temperature for half an hour, 20 g of diphenylmethane diisocyanate was added and dissolved in 30 g of toluene, and the mixture was fully mixed, refluxed at 80° C. for 5 h, and concentrated to half of the original volume by vacuum distillation, 100 ml of petroleum ether was added thereto to precipitate the product, and after standing, the supernatant was poured out, and 50 ml of chloroform was added thereto to dissolve. All solvents were removed by rotary evaporation to obtain isocyanate-terminated polybutadiene.
[0127] (3) Mix 1 g of the above polyacrylate with 2.5 g of isocyanate-terminated polybutadiene, add 2 g of anhydrous toluene to adjust the viscosity to a suitable value for scraper coating, stir at room temperature for 30 min, and remove bubbles in vacuum to obtain an optically transparent adhesive.
[0128] A method for preparing a polyacrylate cured product (ITPB-PA-6) based on diphenylmethane diisocyanate polybutadiene crosslinking comprises the following steps:
[0129] The optically transparent adhesive was coated on a 40 μm thick release film, and the coated sample was placed in a fume hood overnight (i.e., at room temperature for 12 hours), and then cured at 100° C. for 2 hours to obtain a 200 μm thick polyacrylate cured product (ITPB-PA-6) based on diphenylmethane diisocyanate polybutadiene cross-linking.
[0130] Example 7
[0131] A high-toughness optical transparent adhesive for folding screens, comprising the following components: 3.5 g of isocyanate-terminated polybutadiene, 1 g of polyacrylate, and 2 g of organic diluent toluene;
[0132] The isocyanate-terminated polybutadiene is prepared from the following raw materials in parts by weight: 10 g of hydroxyl-terminated polybutadiene, 20 g of diphenylmethane diisocyanate, and 60 g of solvent A, toluene;
[0133] The polyacrylate is prepared from the following raw materials in parts by weight: 80 g of ethyl acrylate, a first monomer of acrylic esters, 0.15 g of acrylamide, a second monomer of acrylic esters containing active hydrogen, 2.5 g of azobisisovaleronitrile, an initiator, and 50 g of ethyl acetate, a solvent B.
[0134] The method for preparing the above-mentioned high-toughness optically transparent adhesive for folding screens comprises the steps of:
[0135] (1) 80 g of ethyl acrylate, 0.15 g of acrylamide, and 2.5 g of azobisisovaleronitrile were dissolved in 50 g of ethyl acetate, placed in a three-necked flask equipped with a spherical condenser, heated to 80°C for 12 h under reflux, concentrated by rotary evaporation to half of the initial volume, and then precipitated with methanol to precipitate the product. After standing, the supernatant was poured out, and 10 ml of chloroform was added to dissolve it. All solvents were removed by rotary evaporation to obtain polyacrylate. The yield was 81%.
[0136] (2) 10 g of hydroxy-terminated polybutadiene was placed in a 100 ml three-necked flask, 30 g of toluene was added thereto, and after stirring at room temperature for half an hour, 20 g of diphenylmethane diisocyanate was added and dissolved in 30 g of toluene, and the mixture was fully mixed, refluxed at 80° C. for 5 h, and concentrated to half of the original volume by vacuum distillation, 100 ml of petroleum ether was added thereto to precipitate the product, and after standing, the supernatant was poured out, and 50 ml of chloroform was added thereto to dissolve. All solvents were removed by rotary evaporation to obtain isocyanate-terminated polybutadiene.
[0137] (3) Mix 1 g of the above polyacrylate with 3.5 g of isocyanate-terminated polybutadiene, add 2 g of anhydrous toluene to adjust the viscosity to a suitable value for scraper coating, stir at room temperature for 30 min, and remove bubbles in vacuum to obtain an optically transparent adhesive.
[0138] The preparation method of polyacrylate cured product (ITPB-PA-7) based on diphenylmethane diisocyanate polybutadiene crosslinking comprises the following steps:
[0139] The optically transparent adhesive was coated on a 40 μm thick release film, and the coated sample was placed in a fume hood overnight (i.e., at room temperature for 12 hours), and then cured at 100° C. for 2 hours to obtain a 200 μm thick polyacrylate cured product (ITPB-PA-7) based on diphenylmethane diisocyanate polybutadiene cross-linking.
[0140] Example 8
[0141] A high-toughness optical transparent adhesive for folding screens, comprising the following components: 4.5 g of isocyanate-terminated polybutadiene, 1 g of polyacrylate, and 2 g of organic diluent toluene;
[0142] The isocyanate-terminated polybutadiene is prepared from the following raw materials in parts by weight: 10 g of hydroxyl-terminated polybutadiene, 20 g of diphenylmethane diisocyanate, and 60 g of solvent A, toluene;
[0143] The polyacrylate is prepared from the following raw materials in parts by weight: 80 g of ethyl acrylate, a first monomer of acrylic esters, 0.15 g of acrylamide, a second monomer of acrylic esters containing active hydrogen, 2.5 g of azobisisovaleronitrile, an initiator, and 50 g of ethyl acetate, a solvent B.
[0144] The method for preparing the above-mentioned high-toughness optically transparent adhesive for folding screens comprises the steps of:
[0145] (1) 80 g of ethyl acrylate, 0.15 g of acrylamide, and 2.5 g of azobisisovaleronitrile were dissolved in 50 g of ethyl acetate, placed in a three-necked flask equipped with a spherical condenser, heated to 80°C for 12 h under reflux, concentrated by rotary evaporation to half of the initial volume, and then precipitated with methanol to precipitate the product. After standing, the supernatant was poured out, and 10 ml of chloroform was added to dissolve it. All solvents were removed by rotary evaporation to obtain polyacrylate. The yield was 81%.
[0146] (2) 10 g of hydroxy-terminated polybutadiene was placed in a 100 ml three-necked flask, 30 g of toluene was added thereto, and after stirring at room temperature for half an hour, 20 g of diphenylmethane diisocyanate was added and dissolved in 30 g of toluene, and the mixture was fully mixed, refluxed at 80° C. for 5 h, and concentrated to half of the original volume by vacuum distillation, 100 ml of petroleum ether was added thereto to precipitate the product, and after standing, the supernatant was poured out, and 50 ml of chloroform was added thereto to dissolve. All solvents were removed by rotary evaporation to obtain isocyanate-terminated polybutadiene.
[0147] (3) Mix 1 g of the above polyacrylate with 4.5 g of isocyanate-terminated polybutadiene, add 2 g of anhydrous toluene to adjust the viscosity to a suitable value for scraper coating, stir at room temperature for 30 min, and remove bubbles in vacuum to obtain an optically transparent adhesive.
[0148] The preparation method of polyacrylate cured product (ITPB-PA-8) based on diphenylmethane diisocyanate polybutadiene crosslinking comprises the following steps:
[0149] The optically transparent adhesive was coated on a 40 μm thick release film, and the coated sample was placed in a fume hood overnight (i.e., at room temperature for 12 hours), and then cured at 100° C. for 2 hours to obtain a 200 μm thick polyacrylate cured product (ITPB-PA-8) based on diphenylmethane diisocyanate polybutadiene cross-linking.
[0150] Comparative Example 1
[0151] Synthesis of triisocyanate cross-linked polyacrylate (HDI-PA-1)
[0152] 1 g of triisocyanate curing agent was added to 1 g of polyacrylate (the raw material composition and preparation method of polyacrylate were the same as those in Example 1), and the mixture was mixed evenly at room temperature. The concentration of the mixed solution was adjusted to 1500 mPa·s with anhydrous toluene, and the mixture was defoamed in vacuo to obtain a transparent adhesive.
[0153] The transparent adhesive was coated onto a 40 μm thick release film, which was placed in a fume hood at room temperature for 12 h, and finally cured in a vacuum oven at 100° C. for 2 h to obtain a triisocyanate-crosslinked polyacrylate cured product (HDI-PA-1) with a thickness of 200 μm.
[0154] Test example
[0155] The mechanical properties of the polyacrylate cured products prepared in Examples 1-8 and Comparative Example 1 were tested. The results are shown in Tables 1 and Figure 6-7 shown.
[0156] Table 1 Mechanical properties of different polyacrylate cured products
[0157]
[0158] From Table 1, we can see that:
[0159] (1) The polyacrylate cured products prepared in Examples 1-8 can all pass the dynamic bending test of 300,000 times. Meanwhile, HDI-PA-1 without the addition of the isocyanate-terminated polybutadiene crosslinker cannot pass the test, indicating that the introduction of polybutadiene can effectively improve the toughness of the material and meet the requirement of 200,000 dynamic bending of the folding screen.
[0160] (2) In Examples 1-4, the same mass of cross-linking agent terminal isocyanate polybutadiene was added, and the shear creep of sample ITPB-PA-4 was as low as 15.3%, which was lower than 137.6% of the comparative example HDI-PA-1. Increasing the cross-linking density improves the creep resistance of the material; the polybutadiene macromolecular cross-linking agent can introduce rubber components into the material, enhance the toughness of the material, and thus improve the bending resistance of the material. As a result, the elongation at break is also improved. Compared with 12% of HDI-PA-1 without adding terminal isocyanate polybutadiene, the lowest ITPB-PA-4 in Examples 1-4 reached 33%, which meets the high toughness requirements of the folding screen for 180-degree bending and folding.
[0161] (3) It can be seen from Examples 5-8 that with the increase in the amount of cross-linking agent terminal isocyanate polybutadiene, the shear creep of the acrylic ester cured product cross-linked with terminal isocyanate polybutadiene gradually decreases. As the content of the cross-linking agent increases, the degree of cross-linking increases, the shear creep of the material decreases, and the creep resistance increases. Among them, ITPB-PA-8 has the best creep resistance of 55.7%, which is significantly improved compared to the creep resistance of the acrylic ester (HDI-PA-1) without the addition of terminal isocyanate polybutadiene. At the same time, the elongation at break gradually decreases, and the tensile strength gradually increases; among them, ITPB-PA-5 has the largest elongation at break and the lowest tensile strength, which is 29% and 0.8MPa.
[0162] Figure 6 It is a comparison chart of the creep properties of polyacrylate cured products prepared in Examples 1-4 and Comparative Example 1. It can be seen from the figure that sample ITPB-PA-4 has the best creep resistance of 15.3%, is not prone to creep under the action of external force, has the smallest creep amount, and meets the creep resistance requirements of the folding screen.
[0163] Figure 7 This is a dynamic thermomechanical analysis comparison chart of the polybutadiene cross-linked acrylate cured product (ITPB-PA-1) in Example 1. From the maximum peak of the G" curve, it can be concluded that the glass transition temperature (Tg) of ITPB-PA-1 is -50°C. The commonly used model in the market is 8146-2, and the lowest glass transition temperature is -40°C. Its cold resistance is better than that of OCA on the market, and it has good low temperature resistance, which can meet the cold resistance requirements of the folding screen.
Claims
1. A high-toughness optically transparent adhesive for folding screens, characterized in that: The invention comprises the following components: isocyanate-terminated polybutadiene, polyacrylate and an organic diluent; the mass ratio of the isocyanate-terminated polybutadiene to the polyacrylate is 1-4.5:1; The isocyanate-terminated polybutadiene is prepared from the following raw materials in parts by weight: 5-15 parts of hydroxyl-terminated polybutadiene, 10-30 parts of isocyanate compounds, and 50-70 parts of solvent A; The isocyanate compound is one or a combination of two or more of diphenylmethane diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate or toluene diisocyanate; the solvent A is one or a combination of two or more of toluene, acetone, methanol, ethanol, tetrahydrofuran, cyclohexane, ethyl acetate, isopropanol, dichloromethane or chloroform; The polyacrylate is prepared from the following raw materials in parts by weight: 40-80 parts of a first acrylate monomer, 0.15-10 parts of a second acrylate monomer containing active hydrogen, 0.025-3.725 parts of an initiator, and 40-60 parts of a solvent B; The first acrylate monomer is one or a combination of two or more selected from methyl acrylate, ethyl acrylate, n-butyl methacrylate, isobutyl methacrylate, n-octyl acrylate, methyl methacrylate, ethyl methacrylate, isopropyl methacrylate, hexyl methacrylate, isooctyl acrylate or glycidyl methacrylate; the second acrylate monomer containing active hydrogen is one or a combination of two or more selected from acrylamide, acrylic acid, hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxybutyl acrylate, 2-hydroxybutyl acrylate, hydroxypropyl methacrylate, hydroxyhexyl acrylate or hydroxyethyl methacrylate; the solvent B is one or a combination of two or more selected from ethyl acetate, petroleum ether, methanol, ethanol, dichloromethane, toluene, anhydrous ether or tetrahydrofuran; The method for preparing the high-toughness optically transparent adhesive for folding screens comprises the steps of: (1) In solvent A, terminal hydroxyl polybutadiene and isocyanate compound are subjected to addition reaction to prepare terminal isocyanate polybutadiene; (2) In solvent B, under the action of an initiator, a first acrylate monomer and a second acrylate monomer containing active hydrogen undergo a free radical polymerization reaction to prepare a polyacrylate; (3) Evenly mix the isocyanate-terminated polybutadiene, polyacrylate and organic diluent, and remove bubbles to obtain an optically transparent adhesive.
2. The high-toughness optically transparent adhesive for folding screens according to claim 1, characterized in that: The ratio of the mass of the organic diluent to the total mass of the isocyanate-terminated polybutadiene and the polyacrylate is 1:1-3.
3. The high-toughness optically transparent adhesive for folding screens according to claim 1, characterized in that: The organic diluent is one or a combination of two or more of toluene, tetrahydrofuran, 1,4-dioxane, dichloromethane, chloroform or anhydrous ether.
4. The high-toughness optically transparent adhesive for folding screens according to claim 1, characterized in that: Hydroxyl-terminated polybutadiene has the following structure: Among them, x=1-1000, y=1-200, z=1-100.
5. The high-toughness optically transparent adhesive for folding screens according to claim 1, characterized in that: The initiator is one or a combination of two or more of azobisisobutyronitrile, azobisisovaleronitrile, azobisisoheptanenitrile, cyclohexanone peroxide, dibenzoyl peroxide or tert-butyl hydroperoxide.
6. The high-toughness optically transparent adhesive for folding screens according to claim 1, characterized in that: Includes one or more of the following conditions: i. In step (1), the addition reaction temperature is 60-150° C., and the addition reaction time is 5-12 h; ii. In step (1), the post-treatment method of the reaction solution obtained by the addition reaction is as follows: the reaction solution is concentrated to half of the original volume by rotary evaporation, and petroleum ether is added to precipitate a solid product; the solid product is taken and dissolved by adding chloroform; and then all the solvent is removed by rotary evaporation to obtain the isocyanate-terminated polybutadiene; iii. In step (2), the free radical polymerization reaction temperature is 20-90° C. and the reaction time is 5-12 h; iv. In step (2), the post-treatment method of the reaction solution obtained by the free radical polymerization reaction is as follows: the reaction solution is concentrated by rotary evaporation to half of the original volume, methanol is added to precipitate a solid product; the solid product is taken and dissolved by adding chloroform; and then all the solvent is removed by rotary evaporation to obtain polyacrylate; v. In step (3), the preparation of the optically transparent adhesive comprises the steps of: mixing the isocyanate-terminated polybutadiene, polyacrylate and an organic diluent, stirring at room temperature for 0.5-2 hours, and then degassing in vacuum to obtain the optically transparent adhesive.
7. Application of the high-toughness optically transparent adhesive for folding screens as described in any one of claims 1 to 6 in folding screens.
8. The use of the high-toughness optically transparent adhesive for folding screens according to claim 7, characterized in that: The curing method of the optically clear adhesive is as follows: curing at room temperature for 10-15 hours, and then curing at 100-120°C for 1-8 hours.
Citation Information
Patent Citations
LOCA (liquid optical clear adhesive) for full-attached module and preparation method of LOCA
CN104231996A
Polybutadiene-acrylic ester, preparation method thereof and application
CN106496390A
Acrylate-Terminated Urethane Polybutadienes From Low-Monomer 1:1 Monoadducts From Reactive Olefinic Compounds and Diisocyanates and Hydroxy-Terminated Polybutadienes for Liquid Optically Clear Adhesives (LOCAs)
CN106893546A